Cardiac arrhythmia triggered by diuretic-induced hyponatremia - Lu, HT (Malays Fam Physician, 2019)
Diuretics have a long and distinguished history in the treatment of hypertension and heart failure. Clinical practice guidelines recommend that diuretics should be considered to be as suitable as other antihypertensive agents for the initiation and maintenance of antihypertensive treatment. However, diuretics may potentially cause electrolyte disturbances and metabolic side effects. Diuretic-induced hyponatremia is probably more prevalent than generally acknowledged. We present an unusual case of indapamide-induced hyponatremia and hypokalemia complicated by cardiac arrhythmia. The adverse drug reaction was reversible and non-life-threatening, but this case serves as a reminder that careful evaluation and constant monitoring are necessary when prescribing diuretics.